MON-437 False Positive I-131 Uptake - Yadav, Pavan Rajendra (J Endocr Soc, 2020)
Background Iodine has high specificity for thyroid tissue hence it plays very important role is management for differentiated thyroid cancer. Despite its high specificity and sensitivity, false-positive I-131 uptake could be seen on whole body scan (WBS). We are presenting a case of false positive intense uptake in lung due to bronchiectasis. Clinical case Patient is a 78-year-old Asian female who initially present with left sided 5.8 cm thyroid nodule. The fine needle aspiration was performed, and the cytology came back as Bethesda category III. Per our institute protocol a molecular mutation panel was sent, which came back with NRAS mutation. She underwent total thyroidectomy and the histology showed 6.2 cm Follicular carcinoma with extensive angioinvasion, oncocyte type. She received adjuvant 165.2 mci of RAI. Per protocol she had a one-week I-131whole body scan. There was intense abnormal uptake in left mid and upper chest. The stimulate thyroglobulin with a TSH of >100mcIU/ml was only 0.17 ng/dl with Tab negative. Patient subsequently had a PET CT which showed a faint diffuse FDG activity noted in the cystic bronchiectasis predominantly in the left apex, lingula, and right middle lobe. Patient informed us that she has history of pulmonary tuberculosis in 1970’s for which she was successfully treated in her home country. We had 10-year-old chest X-ray which showed stable cystic bronchiectasis lesion in the region of intense uptake. Discussion Although I131 whole body scan has high specificity and sensitivity but physician should be aware of potential false positive uptake to avoid unnecessary intervention. In a retrospective evaluation (i) the most common non-thyroid conditions included were bronchiectasis, lung infection, subcutaneous injection into gluteal fatty tissue, aortic calcification, benign bone cyst, vertebral hemangioma, recent nonthyroidal surgical procedure site, rotator cuff injury, mature cystic teratoma and ovarian follicle cyst). The accumulation of the bronchial secretion is the proposed mechanism of the high false positive uptake in bronchiectasis. Endnotes (i) Mol Imaging Radionucl Ther 2018; 27:99–106 DOI:10.4274/mirt.37450